Self Medication Pattern Among Elderly Patients of North India Public Hospital:A Hospital Based Questionnaire Appraisal - M, Mandavi; Tiwari, Pramil; Kapur, Vinay (Indian Journal of Pharmacy Practice)
Self-medication is an economical choice of treatment for common self-limiting illnesses. Major problems related to this are wastage of resources, increased resistance of pathogens, and health hazards like adverse reaction. Elderly patients are more likely to self medicate themselves in view of the multiplicity of disorder they may have. The aim of the study was to access the self-medication pattern among elderly inpatients in the medicine wards of the public hospital, Chandigarh. Prospective questionnaire-based interview covered 515 elderly patients. Any medication(s) taken without a prescription, prior (average of two and half months) to hospitalization were considered selfmedication. Approximately 63% patients reported use of the non-prescription drugs/complementary medicine. Out of these 323 patients, 45.8% of the patients had used allopathic medications for treatment of their ailments without prescription or any medical advice. 18% of patients followed homeopathic and 30.3% patients were using ayurvedic medicines as self-medication. 6% patients used household remedies for self treatment. The number of patients who reported gastrointestinal disorders like gastric pain, acidity, diarrhea, and constipation as the most frequently selftreated symptom was 226. The other major reported illnesses include, fever in 110 and cough & cold in 95 patients. Analgesics/antipyretics like diclofenac, paracetamol and aspirin were the frequently used drugs. The drug for the treatment of acidity, flatulence and dyspepsia ranked second was antacids. On the basis of the feedback from 227 patients, the most probable reason for practicing self-medication was financial limitation. The prevalence of selfmedication is quite high. In addition to allopathic drugs, a medicine from other systems of medicine was also commonly used for self-medication. Strict legislation regarding the accessibility of these drugs and education of the community on self-medication is essential for effective use of medicines is required.